Improving value in health care : measuring quality (Organisation for Economic Co-operation and Development, 2010)
Are breast cancer survival rates higher in the United States than in the United Kingdom and France? Are a patient\'s chances of dying within 30 days after admission to a hospital with a heart attack lower in Canada than in Korea? Are surgeons in some countries more likely to leave foreign bodies behind after operations or make accidental punctures or lacerations rates when performing surgery? The need for answers to these kinds of questions and the value of measuring the quality of health care are among the issues addressed in this publication. Many health policies depend on our ability to measure the quality of care accurately. Governments want to increase patient-centeredness, improve co-ordination of care, and pay providers of high-quality care more than those who underperform. However, measuring the quality of health care is challenging. The OECDs Health Care Quality Indicator project has overcome some of the problems, though many remain. If policy makers are serious about improving the body of evidence on the quality of care, they need to improve their health information systems. This publication describes what international comparable quality measures are currently available and how to link these measures to quality policies such as accreditation, practice guidelines, pay-for-performance, national safety programmes and quality reporting.Table of Content : AcronymsExecutive summary IntroductionChapter 1. Why Do We Need Information on Health Care Quality?-1.1. Co-ordination of care-1.2. Prevention-1.3. Patient-centered care-1.4. Health technology assessment (HTA) and clinical evaluations-1.5. Safety the quality chasm persists -1.6. Pay for performance-1.7. Quality-led governance-1.8. The cross-national character of quality-led governance-1.9. Strategy-based quality indicator benchmarking systemsChapter 2. What Does Existing Data on Health Quality Show?-2.1. OECD Health Care Quality Indicators (HCQI) Project: history and background-2.2. Primary care-2.3. Acute care for chronic conditions using coronary artery disease (CAD) as an example-2.4. Mental health-2.5. Cancer care-2.6. Patient safety-2.7. Patient experienceChapter 3. How Can National Health Information Infrastructures Improve the Measurement of Quality of Care?-3.1. Reviewing developments in national health information infrastructures-3.2. The five main types of information sources for population-based quality indicators-3.3. Synthesising the lessons learned -3.4. Improving health information systems and data infrastructures-3.5. Promoting the information agendaChapter 4. How Can Quality Indicators Be Used for Health System Improvement?-4.1. Health system inputs-4.2. Health system design-4.3. Health system and services monitoring -4.4. Health system improvementChapter 5. Conclusions and Recommendations
OECD health policy studies, ISSN 2074-3181
Keywords: Program Evaluation; zdravotní péče - kvalita, dosažitelnost a hodnocení; kvalita zdravotní péče; Quality of Health Care; hodnocení programu; ukazatele kvality zdravotní péče; Health Information Management; řízení zdravotnických informací; Health Care Quality, Access, and Evaluation; Quality Indicators, Health Care; management, organizace a řízení zdravotnictví